ANALISIS HUKUM TERHADAP PRODUSEN MINYAK GORENG DI SULAWESI UTARA (STUDI KASUS TENTANG DUGAAN PELANGGARAN TERHADAP PASAL 4 DAN PASAL 5 UNDANG-UNDANG NO.5 TAHUN 1999) - Tulandi, Edwin Steven ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study aimed at investigating the position of PT. Agro Makmur Raya and PT. Multi Nabati Sulawesi in the dedision made by KPPU, which was the Decision Number 24IKPPU-V2009 and finding out whether the verificationof the evidence by the KPPU in the dedision has been pursuant to the existing positive law in Indonesia. It was a descriptive and analytic study because it described comprehensivelyand systematically the legal principles, the legal norms, the legal administration of laws and doctrines related to the suspected breach of the articles 4 and 5 of the Act Number 5 of 1999. Considering its approach, it was normative and juridical study because it was based on literature study in obtaining secondary data of the legal area and simultaneouslyan in-field study was conducted to compled the data. The results of the study showed that PT. Agro Makmur Raya and PT. Multi Nabati Sulawesi related to the decision made by the KPPU was positioned as breaching the articles 4 and 5 of the Act Number 5 of 1999 because the requirements of the articles 4 and 5 of the Act Number 5 of 1999 have been fulfilled that PT. Agro Makmur Raya and PT. Multi Nabati Sulawesi have through their market leaders established indirect agreement with other frying oil producers by organizing meetings and communication about price, production capacity and production cost structure that the decrease in CPO's price was not followed by the decrease in the frying oil's price and because of that the action by PT. Agro Makmur Raya and PT. Multi Nabati Sulawesi could be considered as having breahced the articles 4 and 5. The problem was that there was lack of the evidence that must be submitted to the KPPU that the KPPU used indirect evidience pursuant to the Act Number 5 of 1999, the verse 42 of of the Act Number of 1999 and the verse 2 of the Article 64 of the KPPU's regulation on evidence. Thus it could be seen that the indirect evidence represented indicative evidence only and based on the minimum limit evidence 2 evidence were at least required following the Act Number 5 of 1999.